The regulation of totipotency transcription: Perspective from in vitro and in vivo totipotency - Xu, Haiyan; Liang, Hongqing (Frontiers in Cell and Developmental Biology, 2022)
Totipotency represents the highest developmental potency. By definition, totipotent stem cells are capable of giving rise to all embryonic and extraembryonic cell types. In mammalian embryos, totipotency occurs around zygotic genome activation period, which is around the two-cell stage in mouse embryo, or four to eight cell stage in human embryo. Currently with the development of in vitro totipotent like models and the advances in small scale genomic methods, in-depth mechanistic understanding of the totipotency state and regulation was enabled. In this review, we explored and summarized the current views about totipotency from various angles including genetic and epigenetic aspects. This will hopefully formulate a panoramic view of totipotency state from the available research works up to now, and will also delineate the potentially features and hypothesis on totipotency for future research works.